IDDF2019-ABS-0215 Antimicrobial prophylaxis after hepatic resection for hepatocellular carcinoma: a propensity score matching study. (7th June 2019) - Chen, Zebin; Chen, Shuling; Liang, Ruiming; Peng, Zhenwei; Peng, Sui
Abstract : Background: Hepatic resection (HR) is one of the curative treatments for hepatocellular carcinoma (HCC) and infection is a common complication after HR. For clean-contaminated surgery, the guideline recommends only preoperative prophylactic antibiotics; however, antibiotics are frequently used postoperatively in reality. We investigate whether postoperative prophylactic antibiotics can reduce infection for HR. Methods: From January 2009 to December 2017, patients whom underwent HR for Barcelona Clinic Liver Cancer (BCLC) stage 0/A/B HCC in three tertiary referral centers were included in the study. Patients were divided into two groups according to whether they used prophylactic antibiotics postoperatively or not. One group did not use antibiotics after HR (group A), and the other group did (group B). The infection rates were estimated and compared between the two groups before and after matching the propensity scores. Results: In total, 1049 patients were included, with 273 patients in group A and 776 patients in group B. The median days of postoperative antibiotic use in group B is 5.0 days (interquartile range [IQR], 3.0–7.0 days). The infection rate was 27.5% and 6.8% in group A and B, respectively ( P <0.001). Prothrombin time > 14 seconds (OR 2.05, 95% CI 1.10–3.83), albumin < 35 g/L (OR 1.89, 95% CI 1.01–3.54) and postoperative prophylactic antibiotics (OR 0.20, 95% CI 0.14–0.30) were independently associated with infection. After matching the propensity scores, the infection rates in the group A (n=260) and B were 28.1% and 8.5%, respectively ( P <0.001). Conclusions: Postoperative prophylactic antibiotics can reduce the incidence of infection after HR for HCC.